Efficacy of Usnea sp. Extracts in Preventing Biofilm Formation by Bacillus Species Isolated from Soaking Liquor Samples - (:unkn) unknown (AMER LEATHER CHEMISTS ASSOC, 2020)
Bacteria forms biofilm to be resistant to antibacterial agents and other unfavorable environment as compared to planktonic bacterial cells. Due to resistance of bacterial biofilms to commonly used antimicrobial agents and adverse effects of these biofilms in different industries, potential natural compounds which can inhibit bacterial biofilms have attracted more attention in recent years. Lichens are known to have unique secondary metabolites with various biological activities including anti-biofilm properties. Therefore, Bacillus toyonensis, Bacillus mojavensis, Bacillus subtilis, Bacillus amyloliquefaciens, Bacillus velezensis, Bacillus cereus, and Bacillus licheniformis, isolated from soak liquor samples in the previous study, were tested for their ability to form biofilm in this study. Biofilm-forming Bacillus species were detected as B. subtilis, B. amyloliquefaciens, and B. velezensis. The anti-biofilm effect of the acetone extracts of Usnea sp. was evaluated at various concentrations against these biofilm-forming isolates. The anti-biofilm effect of acetone extracts of Usnea sp. against B. subtilis and B. amyloliquefaciens was observed at the concentration of 5 mu g/mL by inhibition ratios of 62.75% and 72.72%, respectively. In addition, biofilm formation of B. velezensis was inhibited by the treatment with 1.25 mu g/mL extracts at a 62.69% inhibition rate. Biofilm formations of B. amyloliquefaciens and B. velezensis were also suppressed by the extracts at varying percentages of inhibition ranging between 10.11-43.69% and 21.25-46.35%, respectively. This study may provide an alternative approach to overcome the biofilm formation and bacterial resistance to the antibacterial agents in the leather industry.
Keywords: TO-CELL COMMUNICATION; BACTERIAL-POPULATIONS; HALOPHILIC BACTERIA; LEATHER; HIDE; SALT; SUSCEPTIBILITY; CHLORIDE